Transcriptional changes in chick wing bud polarization induced by retinoic acid. Issue 9 (24th July 2017) - Pickering, Joseph; Wali, Neha; Towers, Matthew
Abstract : Background : Retinoic acid is implicated in the induction of the gene encoding Sonic hedgehog (Shh) that specifies anteroposterior positional values and promotes growth of the developing limb bud. However, because retinoic acid is involved in limb initiation, it has been difficult to determine if it could have additional roles in anteroposterior patterning. To investigate this, we implanted retinoic acid–soaked beads to the anterior margin of the chick wing bud and performed microarray analyses prior to onset of Shh expression.Results: Retinoic acid up‐regulates expression of Hoxd11‐13 that encode transcription factors implicated in inducing Shh transcription and that are involved in digit development. In our assay, retinoic acid induces Shh transcription and, consequently, a new pattern of digits at a much later stage than anticipated. Retinoic acid represses many anteriorly expressed genes, including Bmp4, Lhx9, Msx2, and Alx4 . We provide evidence that retinoic acid influences transcription via induction of dHAND and inhibition of Gli3 to establish a new anteroposterior pre‐pattern. We show that transient exposure to retinoic acid can suppress distal development and expedite cells to transcriptionally respond to Shh.Conclusions: Our findings reveal how retinoic acid and Shh signaling could cooperate in anteroposterior patterning of the limb. Developmental Dynamics 246:682–690, 2017 . © 2017 Wiley Periodicals, Inc. Key Findings: Retinoic acid‐soaked beads implanted into the anterior margin of an early chick wing bud can induce a new pattern of digits with only a 12 h requirement of Shh expression. Retinoic acid induces dHAND and inhibits Gli3 expression to establish a new antero‐posterior pre‐pattern. Retinoic acid induces expression of 5'Hoxd genes independently of Shh signalling. Retinoic acid represses many anteriorly‐expressed genes. Retinoic acid expedites the response of cells to Shh signalling.